Deglobalization and economic growth the impact of international trade and FDI on real GDP in ASEAN-8 - Bacoy, Samantha B.
The impact of international trade and FDI on economic growth remains an important topic of debate in economic literature and legislature. This research has three objectives. Firstly, to examine the long-run relationship between international trade, FDI, and economic growth using Pedroni panel cointegration. Secondly, to estimate the impact of international trade and FDI on the ASEAN economy using PVAR approach. Thirdly, to establish the direction of causality among the variables using Granger causality. The data used in this study are on 8 ASEAN countries namely, Brunei Darussalam, Cambodia, Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam (ASEAN-8) covering from 2005 to 2019. The empirical results of the Pedroni cointegration suggest the existence of long-run relationships among international trade, FDI, and economic growth. The PVAR test suggests that international trade has a greater impact than FDI on economic growth. Interestingly, the results of the Granger causality show bidirectional causality between trade-economic growth, FDI-economic growth, and trade-FDI. In conclusion, the results of this study indicate that international trade and FDI generate economic growth.